Landscapes, gender, and ritual space : the ancient Greek experience - Cole, Susan Guettel (University of California Press, 2004)
Taking a fresh look at the epigraphical evidence for Greek ritual practice in the context of recent studies of landscape & political organization, Cole illuminates the profoundly gendered nature of Greek cult practice & explains the connections between female rituals & the integrity of the community.